Acetaminophen Reduces Social Pain - DeWall, C. Nathan; MacDonald, Geoff; Webster, Gregory D.; Masten, Carrie L.; Baumeister, Roy F.; Powell, Caitlin; Combs, David; Schurtz, David R.; Stillman, Tyler F.; Tice, Dianne M.; Eisenberger, Naomi I. (Psychological Science, 2010)
Pain, whether caused by physical injury or social rejection, is an inevitable part of life. These two types of pain-physical and social-may rely on some of the same behavioral and neural mechanisms that register pain-related affect. To the extent that these pain processes overlap, acetaminophen, a physical pain suppressant that acts through central (rather than peripheral) neural mechanisms, may also reduce behavioral and neural responses to social rejection. In two experiments, participants took acetaminophen or placebo daily for 3 weeks. Doses of acetaminophen reduced reports of social pain on a daily basis (Experiment 1). We used functional magnetic resonance imaging to measure participants' brain activity (Experiment 2), and found that acetaminophen reduced neural responses to social rejection in brain regions previously associated with distress caused by social pain and the affective component of physical pain (dorsal anterior cingulate cortex, anterior insula). Thus, acetaminophen reduces behavioral and neural responses associated with the pain of social rejection, demonstrating substantial overlap between social and physical pain.